Socialization on TOEFL Listening: Benefits and Strategies for Students at SMA Negeri 3 Pematangsiantar - Eksaulina Simanjuntak; Indah Peronika Siahaan; Imeliana Saragih; Diana Dian Sari Tampubolon; Putri Anastasia Silalahi; Risma Novalina Sagala; Yanti Kristina Sinaga; Sudung Simatupang; Junita Batubara (Jurnal Pengabdian Nusantara, 2026)
This community-based outreach program was conducted to improve Grade XI students’ awareness, skills, and motivation in preparing for the TOEFL Listening section at SMA Negeri 3 Pematangsiantar. As English language proficiency becomes an increasingly essential requirement for global education and career advancement, early exposure to international standardized tests such as TOEFL is critical. The program introduced students to the structure and function of the TOEFL, including its different types (iBT, ITP, and Prediction) and the specific challenges of the Listening section. Students were trained to use effective strategies such as focusing on the final line in dialogues, identifying synonymous phrases in questions and answers, and avoiding traps based on similar sounds. The implementation included interactive presentations, real-time simulations using Google Forms, and guided listening activities with authentic audio. Students participated actively and demonstrated improved engagement, comprehension, and test readiness. The feedback phase indicated that students gained a clearer understanding of TOEFL Listening tasks and increased confidence in approaching listening-based questions. The combination of strategy-based instruction, digital simulations, and supportive discussion helped students overcome initial anxiety and performance gaps. As a result, this outreach initiative successfully equipped students with practical listening tools, increased their motivation to practice independently, and laid the foundation for future TOEFL preparation. It is recommended that similar programs be extended to other schools to support students’ readiness for international English proficiency testing.